From drug abuse to lesbianism: an educational undertone - Princewill ikechukwu Egwuasi; Dr Gertrude J Archibong; Mercy udeme Ette; Joy Omaga (Journal of Educational and Learning Studies, 2021)
The issue of drug abuse and the resultant effects has been on the limelight in recent times. Hence, this paper examined from drug abuse to lesbianism: an educational undertone. The paper highlighted the meaning of drugs and what constitutes drug abuse. It identified the ever several dangers associated with drug abuse in tertiary institutions in Nigeria, where lesbianism was spotted as a major fallout of the negative impacts of drugs on female undergraduates. Furthermore, the act of lesbianism was evaluated, where the modus operandi and factors of the lesbians were showcased. In the end, the paper conceived some therapy that could help in the curtailing or eradicating of this menace in our institutions of higher learning. Among the recommendations of the paper were that every management of tertiary institutions must recognize this as a time bomb waiting for explosion and that sex education should be institutionalized as a GST or GNS course for all freshmen in our institutions. This would go a long way in checkmating this time bomb from exploding.